Cultural, economic and social sustainability of heritage tourism: Issues and challenges - Monika Murzyn-Kupisz (Economic and Environmental Studies (E&ES), 2012)
Taking into consideration diverse possible areas of cultural heritage impact on socio-economic development processes, the author aims to analyse relations between heritage and tourism in the context of the challenges of sustainable development. She investigates the conditions and factors making heritage tourism beneficial to the local community in social and economic terms, while at the same time being not detrimental to the natural environment, the state of preservation of cultural heritage and the necessity of their safeguarding for future generations.
Keywords: 330; cultural heritage; socio-economic development; sustainable development; heritage tourism